Attentional bias toward high-calorie food-cues and trait motor impulsivity interactively predict weight gain. Issue 1 (May 2016) - Meule, Adrian; Platte, Petra
Strong bottom-up impulses and weak top-down control may interactively lead to overeating and, consequently, weight gain. In the present study, female university freshmen were tested at the start of the first semester and again at the start of the second semester. Attentional bias toward high- or low-calorie food-cues was assessed using a dot-probe paradigm and participants completed the Barratt Impulsiveness Scale . Attentional bias and motor impulsivity interactively predicted change in body mass index: motor impulsivity positively predicted weight gain only when participants showed an attentional bias toward high-calorie food-cues. Attentional and non-planning impulsivity were unrelated to weight change. Results support findings showing that weight gain is prospectively predicted by a combination of weak top-down control (i.e. high impulsivity) and strong bottom-up impulses (i.e. high automatic motivational drive toward high-calorie food stimuli). They also highlight the fact that only specific aspects of impulsivity are relevant in eating and weight regulation.